An Adaptive Activity Book in Supporting Inclusive Science Learning for Low-Vision Students - Nur Hidayah; Joko Siswanto; Sumarno (LPPM Undiksha, 2025)
This study was motivated by the limited availability of accessible learning media for students with low vision, which often results in science instruction failing to meet their visual and multisensory learning needs. This condition creates gaps in conceptual understanding and student engagement during learning activities. The aim of this study was to examine the feasibility, practicality, and effectiveness of an adaptive activity book entitled “Energy for All” as an inclusive learning medium. The study employed a research and development design adapted from the ADDIE model. The participant was a fourth-grade student with monocular visual impairment, while the research subjects included one learning media expert and one subject-matter expert. Data were collected through observations, questionnaires, interviews, and tests. Data analysis combined thematic coding for qualitative data and descriptive analysis for quantitative results. The data collection instruments consisted of questionnaire sheets and test items. The results indicate that the adaptive activity book was highly feasible (media validation score of 89% and content validation score of 90.25%), highly practical (average response score of 87.25%), and effective in improving learning activity by 35.3% and learning outcomes by 46.7%. These findings suggest that simple adaptive print media can enhance conceptual understanding, motivation, and participation among students with low vision in science learning, while providing an inclusive instructional alternative that is easy for elementary school teachers to implement. The study implies that the use of adaptive activity books can support more inclusive science learning processes for students with low vision; therefore, teachers are encouraged to integrate similar adaptive instructional materials into everyday classroom practice.